ANALISIS TRANSKRIPTOMIK JALUR SINTESIS KOLESTEROL PADA USUS ZEBRAFISH (DANIO RERIO) YANG DIBERI PAKAN PISANG TONGKA LANGIT (MUSA TROGLODYTARUM) TINGGI ?-KAROTEN SEBAGAI ALTERNATIF PENGOBATAN PENYAKIT DIABETES - Rizki Firdaus, Ahmad
The number of people with diabetes in Indonesia is quite high, where most deaths from diabetes are caused by complications of cardiovascular disease caused by increased levels of cholesterol in the blood. Several studies have shown that plasma cholesterol levels can be lowered by ?-Carotene supplementation. Fe’i bananas are high in ?-Carotene, so they can be a source of food to prevent diabetes. This study aims to identify the relationship between gene expression profiles that play a role in cholesterol synthesis in the intestines of zebrafish induced by diabetes with Fe’i banana supplementation. The study was conducted by analyzing the results of RNA-seq from zebrafish intestines with control (NL), overfeeding (OF) and overfeeding with supplementation of Fe’i banana (OFTL) treatment. Reads from RNA-sequencing was checked for reading quality using the FastQC program. The reads were then trimmed from the adapters and low-quality sequences using the Cutadapt program to obtain a clean reads. Furthermore, the reads were mapped using the BWA program to the Danio rerio GRCz11 reference genome obtained from ENSEMBL. The reads were then quantified using the htseq program. After being quantified, the data were analyzed using DESeq2 R package using R-studio to identify significant differential gene expression. Furthermore, determination of the ontology of genes and pathways that influence the DESeq2 results was carried out using the DAVID gene enrichment program. The results of the differential expression analysis with a statistical parameter limit of log2foldchange of 1 showed that there were 43 genes that were modulated in OF vs NL, 384 genes on OFTL vs NL, and 51 genes on OF vs OFTL. The results of gene enrichment using DAVID showed that the expression of cholesterol synthesis genes (dhcr24, cyp51, hsd17b7, lss, msmo1, sqlea, tm7sf2, hmgcra, and hmgcs) are down-regulated in samples with Fe’i banana supplementation (OFTL). This shows that there is a decrease in the activity of cholesterol synthesis in the intestines of zebrafish caused by the supplementation of Fe’i banana.